Assessment of the efficacy of selected botanicals and insecticides against sucking pests, viz. Bemisia tabaci (Gennadius), Empoasca kerri (Pruthi) and Caliothrips indicus (Bagnall) in mungbean - Abhishek, K Y; Pankaj, K; Pradeep, Y; Meeta, K; Aman, P S; Sudheer, K; Rajeeb, L M; Amit, K; Chaman, K; Vandana, Y; Deepak, K R; Manish, K; et al. (Plant Science Today, 2025)
The present investigation was conducted to evaluate the efficacy of various combinations of chemical insecticides and botanical extracts against major sucking pests of mungbean (Vigna radiata), namely whitefly (Bemisia tabaci), jassid (Empoasca kerri) and thrips (Caliothrips indicus). This study is the first to systematically assess the performance of integrated treatments combining Imidacloprid, Fipronil and Emamectin benzoate with traditional botanicals such as Neem seed kernel extract (NSKE) and Lantana camara leaf extract. Botanical extracts were prepared using standard soaking, grinding and filtration methods. Field applications were done using standardized spraying protocols. Observations were recorded a day before spraying and 3, 7 and 15 days after spraying. Data were analysed using analysis of variance and treatment means were compared using Duncan’s multiple range test (DMRT) at p ≤ 0.05. Results revealed that the combined application of Imidacloprid + Fipronil @ 500 g/ha was the most effective in the treatment of all three pest species. It significantly reduced the whitefly, jassid and thrips populations, achieving a maximum reduction of 71.1 %, 66.9 % and 77.5 % respectively, compared to the control. The combination of Imidacloprid + NSKE (T3) and Imidacloprid + Lantana camara leaf extract (T1) was also notably effective in reducing the number of all types of pests. Other treatments, such as Fipronil + NSKE and Emamectin benzoate combinations, showed moderate control. All treatments were effective as compared to the untreated control, though the rate of efficacy varied across various treatments. Benefit-cost ratio analysis supported the economic feasibility of the combination of Imidacloprid + Fipronil at the rate of 500 g/ha. This study supports the use of botanical extracts in combination with conventional insecticides as a potential strategy for effective pest management in mungbean cultivation. NSKE and Lantana camara have shown promise as eco-friendly alternatives that can replace or reduce the reliance on chemical pesticides and help minimize environmental pollution. These findings contribute to the development of more sustainable integrated pest management (IPM) strategies in mungbean cultivation and may benefit broader agroecosystems by reducing pesticide dependence and environmental contamination.